POST-SIEGE GENOTOXIC HAZARDS IN LAKE LANAO, PHILIPPINES BY MICRONUCLEUS ASSAY - Fema Abamo; Ed Lucille May Ferranco; Annabella Villarino (BIOTROPIA, 2023)
Massive war pollutants brought by Marawi Siege in the Philippines have contaminated the city environs and the surrounding ancient Lake Lanao. Munition residues including heavy metals are reportedly genotoxic hence this study was conducted to determine the post-siege genotoxic hazards posed by the munition pollutants through micronucleus (MN) assay on the slow-moving edible gastropod snails Vivipara angularis Muller (locally known as “suso”) thriving in the lake. MN, a biomarker of genotoxicity was examined and counted in the hemocytes of exposed juvenile and adult snails. Results revealed that MN frequencies (no. of MN/1000 hemocytes) were significantly higher in snails sampled in Lake Lanao lakeshores than in the reference site Lake Dapao. Among adult samples, there was a decreasing trend of MN frequencies with increasing distance from lakeshore fronting warzone ‘ground zero’ where the battle was heaviest (site A) to sampling sites away from it: sites B, C, and D (Lake Dapao) which are 8.15 km, 24.41 km, and 34.45 km, respectively. Moreover, varied patterns of micronucleation were observed between age groups and sites, i.e., in all sites except C, adults had greater MN counts than juveniles which were significant in site A only. Unexpectedly juveniles displayed significantly high MN counts than adults in site C. The elevated MN frequencies in the snail hemocytes exposed to war pollution could be attributed to genotoxic munition residues eroded and washed into the lake water. Moreover, heavy metals which are common components of weaponries were also detected in the snail muscles, although at concentrations within safe levels but continued consumption may be cautioned to avoid biomagnification. Other genotoxins must be present in site C other than munition residues predisposing the juvenile snails. The results are baseline data on the MN frequencies in V. angularis exposed to war pollutants in Lake Lanao which need further investigation. Post-siege genotoxic hazards in the lake by MN assay cannot be ignored, thus local leaders must be informed of the results for possible intervention to protect the health and well-being of the community.